2004
DOI: 10.1158/1078-0432.ccr-0864-02
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Matrix Metalloproteinases in Early-Stage Oral Squamous Cell Carcinoma as Predictive Indicators for Tumor Metastases and Prognosis

Abstract: Results: The expression score of MMP-2 correlated with that of MMP-9 (r ‫؍‬ 0.291; P ‫؍‬ 0.036), MT1-MMP (r ‫؍‬ 0.286; P ‫؍‬ 0.039), and TIMP-2 (r ‫؍‬ 0.257; P ‫؍‬ 0.050). Patients who developed regional lymph node and/or distant metastasis showed significantly higher scores in the expressions of MMP-9 and TIMP-2 than patients without any tumor metastases (P ‫؍‬ 0.036 and P ‫؍‬ 0.043, respectively). Kaplan-Meier analyses as well as univariate analyses using the Cox proportional hazards model showed that expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
0
10

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 23 publications
15
154
0
10
Order By: Relevance
“…Several studies have investigated the role of MMP-9 in oral SCC and demonstrated a relationship between the expression of this gelatinase and tumor aggressiveness (13), a fact permitting the use of this MMP as a prognostic marker for therapeutic purposes. Preclinical trials have shown that SCCs express high levels of MMPs in vivo and that inhibition of these enzymes in vitro and in animal models is associated with invasiveness and metastasis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of MMP-9 in oral SCC and demonstrated a relationship between the expression of this gelatinase and tumor aggressiveness (13), a fact permitting the use of this MMP as a prognostic marker for therapeutic purposes. Preclinical trials have shown that SCCs express high levels of MMPs in vivo and that inhibition of these enzymes in vitro and in animal models is associated with invasiveness and metastasis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have determined that both MMP-2 and MMP-9 are associated with lymph node metastasis (Xie et al, 2004) and poor outcome (Katayama et al, 2004) in HNSCC. In addition, microarray gene expression studies on whole HNSCC tumour samples have identified the overexpression of several MMPs including MMP-2 (Nagata et al, 2003;Chung et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of TIMP-2 are often unchanged between tumors and adjacent normal specimens. Studies have commonly identified MMP-2 and MMP-9 associated with lymph node metastasis 43 and poor outcome 44 in laryngeal cancer.…”
Section: Assessment Of Matrix Metalloproteases In Head and Neck Cancermentioning
confidence: 99%